PRIVATE LIVES, PUBLIC ISSUES: CHILDBEARING EXPERIENCES OF ADOLESCENT MOTHERS IN THE ERA OF HIV AND AIDS IN BHAMBAYI, KWAZULU-NATAL, SOUTH AFRICA - Raniga, Tanusha; Mathe, Sibonsile (Social Work/Maatskaplike Werk, 2011)
In poor communities, where early childbearing is common, adolescent girls are not only prone to HIV infection and economic exclusion, but are subjects of sexual exploitation by older adolescent and adult men. It is also widely acknowledged that sex at an early age and with an older partner has been linked with increased risks of unwanted pregnancies, childbearing and HIV risk (Fawole, Asuzu & Oduntan, 1999; Maharaj, 2006; Manlove, Teery-Humen & Ikramullah, 2006; Manzini, 2001; Rutenberg, Kaufman, MacIntyre, Brown & Karime, 2003). Moreover, in the provinces of Gauteng and KwaZulu-Natal, one in three young mothers are infected with HIV (Hanga, Kubai, Mwaura & Ayanga, 2008:107). A quantitative survey conducted by Manzini in 2001 on childbearing among adolescent girls revealed that of a sample of 796 almost half had already engaged in sex at age 16 and had confirmed unwanted pregnancy. Singh and Darroch (1999) argued that the high incidence of adolescent childbearing in the developing countries is inversely related to socio-economic development and not linked to behavioural and/or sexual choices. However, the complex social dynamics underpinning adolescent childbearing means that the situation is not simply a matter of improving public policy and access to reproductive counselling and health services, but that psycho-social and economic obstacles need to be taken into account (Singh & Darroch, 1999). Additionally, the World Health Organisation (2003) stipulates that gender inequalities, economic hardship and poverty are conditions that create the breeding ground for sexual violence against women and high rates of unwanted adolescent pregnancies. Bhana (2009) takes these arguments further and maintains that what adds to the complexity of this social problem in contemporary South Africa is large-scale social forces underwritten by the legacies of apartheid and colonialism, including persistent poverty, and racial and gender inequalities.